Cost-effectiveness of daratumumab in multiple myeloma treatment: A systematic review - Duyen, Nguyen Thi My; Y, Nguyen Tran Nhu; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: The cost-effectiveness of daratumumab in multiple myeloma treatment is a considerable criterion in clinical practice with tight health budgets. This review aimed to evaluate the cost-effectiveness of daratumumab in the treatment of multiple myeloma. Methods: The systematic review method was conducted under the guidance of PRISMA, identifying through a literature search from 3 databases (Embase, PubMed, and Cochrane) with relevant keywords. Nine articles among 95 found articles, satisfying the inclusion criteria, were analyzed. All studies were conducted in the US and China between 2017 and 2021, assessing the cost-effectiveness of adding daratumumab to current regimens. Results: Most of the studies were from a payer perspective, with ICER of $30,893-$1,445,533/QALY. Daratumumab was found to be cost-effective in 2 studies and not cost-effective in comparison with regimens without daratumumab in 7 remaining studies. Conclusions: The systematic review evaluating the cost-effectiveness of daratumumab in multiple myeloma treatment recorded varied ICER results ranging from $30,893/QALY to $1,445,533/QALY with heterogeneous conclusions about cost-effectiveness, The US and China are the only setting countries. More similar studies in developing countries are required to fully evaluate the cost-effectiveness of daratumumab in the treatment of multiple myeloma.